2020
DOI: 10.1089/vbz.2019.2542
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Ljungan Virus in Small Mammals in Europe

Abstract: Ljungan virus (LV), which belongs to the Parechovirus genus in the Picornaviridae family, was first isolated from bank voles (Myodes glareolus) in Sweden in 1998 and proposed as a zoonotic agent. To improve knowledge of the host association and geographical distribution of LV, tissues from 1685 animals belonging to multiple rodent and insectivore species from 12 European countries were screened for LV-RNA using reverse transcriptase (RT-)PCR. In addition, we investigated how the prevalence of LV-RNA in bank vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Ljungan virus (LV), first isolated from a bank vole (Myodes glareolus) by the river Ljungan in Northern Sweden, was defined as a Parechovirus in the family Picornaviridae [1,2]. The isolation of the 87-012 virus was followed by characterization of several different LV strains from humans, voles, other rodents, and birds [3][4][5][6][7][8]. However, it is unclear to what extent LV infection in humans causes symptoms characteristic of Parechovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Ljungan virus (LV), first isolated from a bank vole (Myodes glareolus) by the river Ljungan in Northern Sweden, was defined as a Parechovirus in the family Picornaviridae [1,2]. The isolation of the 87-012 virus was followed by characterization of several different LV strains from humans, voles, other rodents, and birds [3][4][5][6][7][8]. However, it is unclear to what extent LV infection in humans causes symptoms characteristic of Parechovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents and other small mammals were sampled in 14 European countries within the EU FP7 project EDENext and several national research projects [ 23 , 25 , 26 , 27 , 28 , 29 ] ( Table 1 ; Figure 1 ). Rodent necropsy and tissue samplings followed previously established standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction was performed using a phenol–chloroform protocol for liver or lung tissue samples of a large part of the sample collection, as previously described [ 25 ]. Another part of liver samples was homogenized in 500 µL phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate of virus isolation attempts is low even from infected clinical specimens generated under experimental conditions [ 10 , 13 , 14 ]. Ljungan virus has been detected/isolated in several European countries, the USA, and Japan [ 10 , 15 , 16 , 17 , 18 , 19 ]. Genetic analyses of the virus strains showed that LVs can be divided into four genotypes [ 16 , 17 , 20 ].…”
Section: Ljungan Virus In the Picornavirus Familymentioning
confidence: 99%